Analysis of the Influence of Lunar Cycle on the Frequency of Spontaneous Deliveries: A Single-centre Retrospective Study - Laganà, AS; Burgio, MA; Retto, G; Pizzo, A; Sturlese, E; Granese, R; Chiofalo, B; Ciacimino, L; Triolo, O (Kathmandu University Medical Journal, 2015)
Background Man, since ancient times, has been convinced of, and has researched scientific evidence that the barometric and gravitational forces play an important role in structural and biological variation of the planets, influencing the various forms of life. In particular, the synergistic relationships between variations in atmospheric pressure and gravitational forces on human gestation period have been the subject of rigorous observations and statistical calculations, which have not led to a universal conclusion in literature. Objectives The aim of our work was to check whether there is a higher incidence of spontaneous deliveries, during the periods of full Moon than during the other phases of the Moon. Methods We performed a retrospective analysis of 327 non-induced vaginal deliveries in a year, divided by month. We subsequently analyzed the incidence of these deliveries during periods of full Moon Vs other lunar phases. Results We evidenced a statistically significant difference between the annual total spontaneous deliveries happened in full Moon periods Vs all other Moon phases (T= 2,3946; p=0,0256). However, we reported a discordant trend of deliveries in full Moon period, depending on each considered month. Conclusion Since these differences were found both in increase and decrease, it is unacceptable the assumption of a linear correlation between periods of full Moon and increased frequency of spontaneous deliveries. For this reason, our data allow us to conclude that there is no need to increase the number of doctors and midwives in obstetric units during these periods. Kathmandu University Medical Journal Vol.12(4) 2014; 233-237